Discourse analysis and its uses in organizational studies: a study of quotation contexts of Phillips, Lawrence e Hardy (2004) [doi: 10.21529/RECADM.2016004] - Samir Adamoglu de Oliveira; Luciana Godri; Mayla Cristina Costa; Edson Ronaldo Guarido Filho (Revista Eletrônica de Ciência Administrativa, 2017)
This work has as goal to evaluate how the paper of Phillips, Lawrence and Hardy (2004) and their discourse analysis model has been appropriated in the Organizational Studies field. Using a bibliometric measure of quoters and the qualitative analysis of quotation context, this paper describes: (i) the way it was applied empirically in researches, (ii) to what study objects it was applied, (iii) in which thematic areas it was used, and (iv) its repercussion among different theoretical slopes that have used the analytical model. As it was one of the first works to consider the possibility of a discourse analysis within the organizational studies using institutionalism, after 10 years of the publication, the results show perennial as a meta-theoretical base to discuss the theme. Considering those, the present paper proposes a theoretical-methodological model to conduct future discussions about the discourse role in the (re)production of institutional web.   Keywords Discourse analysis; Discourse; Institutions; Quotation contexts.